Pendidikan Khusus Siswa Hiperaktif di Sekolah Dasar Negeri 32 Pondok Kubang Bengkulu Tengah - Linda Marlensi; Sevi Wahdatun; Yuli Astuti; Rica Andela; Jelii Syah Putri (JPT : Jurnal Pendidikan Tematik, 2023)
Education is a very important activity for every human being, whether normal or with special needs. There are 2-4 percent of children in Indonesia who suffer from ADHD/hyperactivity. Hyperactivity is a condition where an individual has problems in paying attention and concentrating on activities or something. The purpose of this study is to look at special education for hyperactive children, especially at State Elementary School 32 Pondok Kubang Bengkulu Tengah. In this study, the author used a qualitative descriptive approach. Data collection techniques in this study used observation and interviews. Research informants were taken using purposive sampling techniques. The results of the study show that at SDN 32 Bengkulu Tengah there is no special teacher to handle ADHD children, even though they do not have a special teacher the teachers there still provide a good education. Teachers at SDN 32 Bengkulu City give report card grades with different KKM between hyperactive children and other children. In addition, the provision of assignments and materials is slightly different between hyperactive children and other children.